(untitled) (Brazilian Journal of Oceanography, 2018)
The freshwater-influenced region of the Patos Lagoon discharge to the Southern Brazilian Shelf (SBS) is a region of complex fluid dynamics. Seasoning and synoptic variable winds and coastal current conditions create an alternating flow pattern. The aim of this paper was to investigate the occurrence of persistent coherent structures in this environment. A numerical approach was chosen to describe the main hydrodynamic features of the region during a climatological year. The open-source finite-element code TelemacMascaret was applied to the three-dimensional domain. In addition the two-equation k-epsilon model described the turbulence mechanisms. The presence of persistent high-turbulent structures was identified within the study area. These occur as a strong curvilinear disturbance characterized by higher turbulent production and dissipation rates, which increase local mixture. As a result, upward circulation flow was observed, which may be due to irregularities in bottom topography associated with wind-induced stress forces. These results increase the information about the circulation structures of the study area by means of numerical modelling analysis.